2006
DOI: 10.1007/s10509-006-9207-8
|View full text |Cite
|
Sign up to set email alerts
|

Photometric Observations and Light Curve Studies of the Semi-Detached Eclipsing Binary R CMa

Abstract: We present observations and light curve analysis of the eclipsing binary R CMa in the narrow band filters v and b. Observations were made during 1993 at Biruni Observatory and the light curves have been analyzed using the Wilson-Devinney light curve interpretation program. Assuming a semi-detached configuration for R CMa, the parameters i, 1 , L 1 , T 2 and A 2 were adjusted for the best fit between the synthesized light curves and observations. Both light curves were fitted well with a lower value of bolometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Sarma et al (1996) derived 7310±100 K, based on the observed B−V value of +0.27 obtained from the light curves of Radhakrishnan et al (1985), and assumed the primary component of R CMa as an F1 star. This value of 7310 K was adopted later by several authors like Varricatt & Ashok (1999) or Mirtorabi & Riazi (2006) in their light-curve analyses and also by BB2011. We repeated the spectrum analysis with T eff fixed to 7300 K using [Fe/H] as a free parameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarma et al (1996) derived 7310±100 K, based on the observed B−V value of +0.27 obtained from the light curves of Radhakrishnan et al (1985), and assumed the primary component of R CMa as an F1 star. This value of 7310 K was adopted later by several authors like Varricatt & Ashok (1999) or Mirtorabi & Riazi (2006) in their light-curve analyses and also by BB2011. We repeated the spectrum analysis with T eff fixed to 7300 K using [Fe/H] as a free parameter.…”
Section: Discussionmentioning
confidence: 99%
“…3, but for the best fit using T eff =7500 K. (1985), and assumed the primary component of R CMa as an F1 star. This value of 7310 K was adopted later by several authors like Varricatt & Ashok (1999) or Mirtorabi & Riazi (2006) in their light-curve analyses and also by BB2011.…”
Section: Discussionmentioning
confidence: 99%